Naskah Ulu Komering: Sebuah Kajian Filologi - M. Affan Ridhollah, Berlian Susetyo, Agus Susilo, Yeni Asmara (LP4MK STKIP PGRI Lubuklinggau, 2024)
For a long time, South Sumatra has had a written tradition in the form of a script written in the Ulu script which developed in the Uluan area. One of the findings of the Komering variant of the Ulu script is found in Tanjung Kukuh Village, West Semendawai District, East Ogan Komering Ulu Regency. The problem of this research is how to describe and analyze the text of the contents of the manuscript. The aim of this research is to describe and understand the contents of Komering's manuscript. The method used is the philological method which presents the text and describes the physical nature of the manuscript to be studied. The results of the research show that this manuscript is made from paper and contains a letter sending money from a student to his teacher from the proceeds of buying and selling.